Analysis of the Implementation of the Prohibition of Littering Waste in Law No. 32 of 2009 Concerning Environmental Protection and Management - Rouli Br Lumban Batu; Bangun, Jacklyn Alona Br; Husin, Muhammad Habib; Br Lumban Batu, Rouli; Purba, Viona Francesca; Manalu, Vivin Silvia Boang; Nababan, Ramsul; Ibrahim, Maulana (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the implementation of the prohibition on littering as regulated in Law Number 32 of 2009. The research method used is analysis of secondary data from various sources such as literature, government reports and related case studies. The results of the analysis show that the implementation of the ban on littering still experiences several obstacles. Factors such as a lack of public awareness of the importance of maintaining a clean environment, limited waste management infrastructure, and a lack of consistent law enforcement are some of the main factors influencing the successful implementation of this Law. In addition, there needs to be a collaborative effort between the government, society and the private sector to increase understanding of the importance of environmental cleanliness and strengthen infrastructure and an effective law enforcement system to ensure compliance with the prohibition on littering. This research suggests the need for a holistic and sustainable approach in addressing this problem, through broader environmental education, stronger policy development, adequate resource allocation, and increased public awareness and participation in keeping the environment clean.